La contaminación ambiental y sus efectos - Chango Chango, Christian Giovanny (2017)
The main objective of this thesis is to expose the problem of environmental pollution and its effects on living beings; The question arises: Is it possible to take measures to minimize the problem that we face? We need to understand that environmental pollution is a growing problem, according to figures from international organizations, it is believed that 80% of environmental pollution in cities comes from CO2 emissions emitted by vehicles that consume fossil fuels. In recent decades, many international and national agencies have addressed this problem. In our country starting in 2015, incentive programs have been implemented for the introduction of ecological vehicles, but for the launch of the ecological vehicle to be beneficial it is important to start with a design that adapts to the needs and unique geography of our country. Throughout this work, basic concepts are explored on: environment, pollution and means of transport; consequently the reader will have a clear and simple idea about the problem of environmental pollution and look for greener mobility options that are being part to the solution of this problem.